Experience of domestic violence by women attending an inner city accident and emergency department. Issue 2 (26th February 2004) - Sethi, D; Watts, S; Zwi, A; Watson, J; McCarthy, C
Abstract : Objectives: To identify the prevalence of domestic violence (DV) (defined as physical abuse perpetrated by intimate partners) in women attending an inner city accident and emergency department and to elicit women's response about being asked routinely about domestic violence in this setting. Methods: 22 nursing shifts were purposefully sampled to be representative of day, night, and weekends. A questionnaire was administered to 198 consenting women who were not intoxicated, confused, or critically ill. Results: The prevalence of acute trauma in women attributable to DV was 1% (95%CI 0.14 to 3.6), the prevalence of lifetime physical abuse was 34.8% (95%CI 28.2 to 41.5), of past year physical abuse was 6.1% (95%CI 3.2 to 10.3), and of lifetime life threatening physical abuse was 10.6% (95%CI 6.3 to 14.9). Seventy six per cent of women felt comfortable about being asked about DV and 60.5% of women felt that they should always or usually be asked about DV in this setting. Conclusion: This cross sectional survey adds to the body of knowledge showing that the prevalence of DV in women attending an accident and emergency department is high. Most women were in favour of being asked, and disclosure was associated with discomfort in few women. This sensitive area of history taking and referral could be undertaken by health professionals using a supportive approach.